Determinant factors affecting quality of reporting in annual report of Malaysian companies / Romlah Jaffar, Sabariah Jamaludin and Mara Riduan Che Abdul Rahman - Jaffar, Romlah; Jamaludin, Sabariah; Che Abdul Rahman, Mara Riduan (Accounting Research Institute (ARI) & Faculty of Accountancy, 2007)
Annual report is one form of communication between managers and stakeholders. Therefore, quality of reporting in annual reports has to be taken into consideration to enable users to make informed decisions. This research investigates factors that influence the quality of reporting in annual reports for the year of 2004 by Malaysian companies. Specifically, this study examines the relationship between quality of reporting with quality of earnings and ownership structure. Agency theory is used as a basis for the study. Quality of reporting is measured using disclosure index, whilst earnings quality is measured by discretionary accrual.